Implementing a maternal mortality surveillance system in Morocco – challenges and opportunities. Issue 3 (4th January 2013) - Abouchadi, S.; Belghiti Alaoui, A.; Meski, F. Z.; De, V.
Abstract Objective To describe the development of the maternal death surveillance system (MDSS) in Morocco and discuss the initial results. Method The nationwide MDSS was implemented in 2009 with the involvement of health professionals and local authorities. It comprises (i) notification of all deaths of women of reproductive age (from 15 to 49 years); (ii) a preliminary survey to identify pregnancy‐related deaths; (iii) a confidential enquiry into all pregnancy‐related deaths. The information thus obtained describes socio‐demographic characteristics of the women, their obstetric and medical history, the mode of delivery, its follow‐up and the medical cause of death. Results From 1st of January 2009 to 31st of December 2009, 3814 deaths of women of reproductive age were recorded, and a total of 436 pregnancy‐related deaths were identified, with 73.4% of those occurring in health facilities. Among the 313 reviewed records, 80.8% were direct obstetric deaths, and 13.5% were classified as indirect. Haemorrhage was the first direct obstetric cause of death (33%). Heart disease was the main indirect obstetric cause of death (39% of indirect causes). Conclusion The Moroccan MDSS is a powerful tool for understanding the causes and circumstances of maternal deaths. However, challenges remain regarding the full coverage of the system, the decentralisation of the data entry and analysis and the completeness of medical records.